(untitled) (LACCEI, 2024)
In this study, a quality management system based on the ISO 9001 standard is proposed for a company that faces the challenge of providing a better quality of service in the face of increased competition. New processes and improvements to existing ones are proposed according to the standard’s requirements. The proposal seeks to improve the ability of the company to provide service that meets customer requirements and consequently increases customer satisfaction. The proposed quality management system also includes the design of mechanisms to monitor the critical quality objectives using statistical control charts. Additionally, a procedure to carry out the continuous improvement of the processes is proposed and presented.